Academic Quality Assurance System Madrasah Targets Madrasah Aliyah Development Project in Central Java - Suratno, Suratno; Zulaeha, Ida (Educational Management, 2019)
This study aims to describe and analyze the successes and weaknesses of the academic quality assurance system for Madrasah Aliyah targeted by MEDP in Central Java. The research approach uses the CIPP evaluative model. The focus of research includes MA Al Irsyad (independent madrasah), MA NU Limpung (integrated madrasah), and MA YSPIS (madrasah pesantren). The instruments used included questionnaires, interview guides, and documentation. The data collected were analyzed using analytical descriptive. Based on the results of the study it was concluded: (1) the need for a comprehensive and intensive socialization in implementing the academic quality assurance system, especially in madrassas in Central Java, and (2) setting the standard quality assurance system in the madrasa environment .